An abstract argumentation framework with comparison criterion - Martínez, Diego C. (2003)
We define an abstract argumentation framework that includes a binary symmetric relation representing argument conflicts, and a function used to evaluate conflicting arguments. In this framework it is clear how defeat relations are constructed, even when the arguments are treated abstractly. We also present a basic classification of comparison criterions and its impact on the set of accepted arguments. Finally, we define the concept of improvements of a comparison criterion and its relation with the fallacies presented in the framework.